2012
DOI: 10.1074/jbc.m111.325258
|View full text |Cite
|
Sign up to set email alerts
|

Independent Structural Domains in Paramyxovirus Polymerase Protein

Abstract: Background: RNA-dependent RNA polymerases of nonsegmented negative-strand RNA viruses (Mononegavirales) harbor multiple catalytic activities. Results: Domain screening and trans-complementation of Paramyxovirus polymerase fragments with dimerization tags identifies independent folding-competent domains. Conclusion: Paramyxovirus polymerases harbor at least two independent domains that lack high-affinity interfaces but require molecular compatibility for bioactivity. Significance: First demonstration of Mononeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 87 publications
4
60
0
Order By: Relevance
“…We observed the same phenomenon for the VSV L protein (27), while other groups of investigators extended these findings to additional paramyxoviruses (28,29) as well Ebola virus (30). Although it seems likely that other regions of the L protein appendage also function as hinges to allow appendage domain movement, these may not be tolerant of large insertions and have yet to be identified.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…We observed the same phenomenon for the VSV L protein (27), while other groups of investigators extended these findings to additional paramyxoviruses (28,29) as well Ebola virus (30). Although it seems likely that other regions of the L protein appendage also function as hinges to allow appendage domain movement, these may not be tolerant of large insertions and have yet to be identified.…”
supporting
confidence: 80%
“…Notably, a recent study showed that paramyxovirus L protein constructs encoding the region upstream and downstream of the hinge region could not reconstitute polymerase activity when they were mixed together unless first fused to dimerization tags (29). No reconstitution of activity was observed when the two L fragments originated from different paramyxoviruses.…”
mentioning
confidence: 99%
“…Importantly, the data we have obtained suggest that, in the context of RSV infection, YM-53403 suppresses overall RSV RNA synthesis but likely does not result in an increase in the levels of abortive RNAs. The location of YM-53403 resistance mutations in variable region 2 of the L gene, combined with structural domain studies of the RSV RNA polymerase indicating a dimerization function in this area (16,28,29), suggests that the compound may allosterically inhibit a tertiary complex essential for transcription or replication. Our findings are consistent with a recent publication showing the ability of a closely related compound, AZ-27, to inhibit a common step in the initiation of RSV transcription and replication (30).…”
Section: Discussionmentioning
confidence: 99%
“…Based on a described pT7-RSV-luciferase minigenome reporter (36), an RSV minigenome construct was generated under the control of the constitutive RNA pol I promoter (pHH-RSV-repl-firefly). Huh-7 cells were cotransfected with this plasmid and plasmids pRSV-L, pRSV-M2-1, pRSV-N, and pRSV-P under CMV promoter control.…”
Section: Methodsmentioning
confidence: 99%